The Role of Psychology in Digital Game Development: A Systematic Literature Study - Veronica Lita Hapsari; Putri Ariatna Alia; Muhammad Ubaidillah; Ananda Setiyowati; Aidha Rachma Noersinda (Jurnal Informatika Ekonomi Bisnis, 2026)
The rapid growth of digital games has increased the need for a strong psychological foundation in the game development process. Psychology plays a crucial role in understanding how players think, feel, stay motivated, and behave, all of which directly influence player engagement and overall gaming experience. This study aims to systematically examine the role of psychology in digital game development through a literature-based approach. A systematic literature review method was employed by selecting reputable scholarly journal articles published within a specific time frame from major academic databases. The selected articles were then analyzed and categorized based on branches of psychology and their applications in game development. The findings indicate that cognitive psychology, motivational psychology, emotional psychology, and social psychology are the most frequently applied fields, particularly in gameplay design, user experience, and player engagement. However, research gaps remain, especially regarding the integration of psychological theories during the early stages of game design. This study highlights the importance of psychology as both a theoretical and practical foundation in digital game development.